Écrire numérique : du texte littéraire entendu comme processus - René Audet (Itinéraires)
Taking into account digital literary writings, I propose to identify their main characteristics that may shed light on these texts’ processes. Building from the notion of apparatus (dispositif) proposed by Ortel, Lojkine and Rykner, this paper aims to seize the operations underpining digital textuality. Among them: negotiation of the media constraint, reticulation, variation, and expansion. Today's textual environment cannot be understood without considering this new emerging poetics.